Overview of AEFI on Survivors and Non-survivors After the Administration of the Covid-19 Vaccine - Ernawati, Ernawati; Nurhayati, Isnaini (KnE Social Sciences, 2023)
Follow-up events post-Covid-19 Vaccine (KIPI) is one of a person’s considerations in deciding whether or not to participate in the Covid-19 vaccine. Adverse events after the Covid-19 vaccine vary widely, several studies have been carried out to look at the characteristics of AEFI after the Covid-19 vaccine. Several things still require study, one of which is the AEFI category for survivors and non-survivors. This study aims to describe the characteristics of post-vaccine adverse events, as well as the AEFI categories for survivors and non-survivors after the Covid-19 vaccine is given. The research design is descriptive with a cross-sectional research method. The research subjects were 128 people in the West Banten Region who had received the Covid-19 vaccine. The data were obtained by using Google-form which had been shared through WhatsApp groups. This research was conducted in December 2021. The data collection technique used in this study was random sampling. The results showed 8 respondents who complained of post-vaccine fever (6.3), 14 complained of dizziness after the vaccine (10.9), 31 complained of muscle pain (24.2), 2 complained of shortness of breath after getting the vaccine (1.2), 2 complained of nausea after getting the vaccine (1.6), and 4 complained of itching all over the body (3,4). The majority of research respondents experienced mild AEFI in both the survivors and the non-survivors. Information related to the lightness of AEFI after the covid vaccine is a mandatory consumption material that must be given to the community; besides that, it can also be used as a basis for the government to set policies. Keywords: AEFI, survivors and non-survivors, COVID-19 vaccine